2019
DOI: 10.1111/exsy.12384
|View full text |Cite
|
Sign up to set email alerts
|

Churn prediction and social neighbour influences for different types of user groups in virtual worlds

Abstract: In virtual worlds (VWs), users have more VW games alternatives, whereas VW companies consequently suffer from high customer turnover rate and low customer loyalty. Therefore, building a churn prediction model to facilitate subsequent churn management and customer retention is important. The churn behaviours and the impact of social neighbour influences to customer churn may be different for different types of users. Accordingly, we segment users into stable, unstable, and solitary user groups according to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…Yet, since large-scale data on customers and their social interactions are more available for current customers than for potential ones, we believe that the use of AI to conduct social network analysis will have higher impact on customer development and retention. This will be particularly relevant to products such as digital games, where customers' social network activities are routinely collected (Liu, Liao, Chen, & Chiu, 2019).…”
Section: Role Of Social Networkmentioning
confidence: 99%
“…Yet, since large-scale data on customers and their social interactions are more available for current customers than for potential ones, we believe that the use of AI to conduct social network analysis will have higher impact on customer development and retention. This will be particularly relevant to products such as digital games, where customers' social network activities are routinely collected (Liu, Liao, Chen, & Chiu, 2019).…”
Section: Role Of Social Networkmentioning
confidence: 99%
“…The most commonly used features describe player behavior and performance, but in addition, social interaction features (Fu et al 2017), cognitive psychological features (Jeon et al 2017), and influence features (Fu et al 2017) have shown to improve the performance of the models. Unsupervised approaches have also been developed, including segmentation of players (Fu et al 2017), difference in social neighbour influence in different user groups (Liu et al 2019), and distinct behavioral profiles associated with churners and active players (Borbora and Srivastava 2012). The sole research we found that used social networks to predict churn, included information from ego-nets showing that loners are much more likely to churn than the socializers, and that the propensity to churn increases with decreased socialization (Borbora et al 2019).…”
Section: Churn Prediction In Online and Mobile Gamingmentioning
confidence: 99%
“…Numerous works predict churn in various domains (Ahn et al 2020). Focusing on games, some utilize only the time spent playing (Milošević, Živić, and Andjelković 2017;Kummer, Nievola, and Paraiso 2018), others use social aspects (Liu et al 2019), some see the problem as time-series (Yang et al 2019), others utilize Natural Language Processing (Kilimci, Yörük, and Akyokus 2020). They use data from different game genres such as Multiplayer Online Battle Arena (MOBA) and Massively Multiplayer Online Role-Playing Game (MMORPG), from different platforms, like desktop and mobile, and target diverse types of players.…”
Section: Related Workmentioning
confidence: 99%